ANALISIS NASKAH DRAMA “BAPAK” KARYA BAMBANG SOELARTO MENGGUNAKAN PENDEKATAN OBJEKTIF - Anggraini, Suhesti; Devi, Wika Soviana (Universitas Madura, 2022)
Drama is a performing art where actors portray a story on stage for an audience. This research analyzes the drama